(untitled) (Journal of Medical Sciences, 2021)
The focus of the current study was on exploring the epidemiological profiles of Trichomonas vaginalis and Candida spp. infections among married women admitted gynaecology clinics in Brack Al-Shati region. 234 of vaginal swab samples were collected and subjected to direct microscopic examination for microorganisms’ characterization. 45 (19.23%) of overall samples examined were found to be T. vaginalis and Candida spp. positives. Occurrence of each infection agent was individually compared. Infection with Candida spp were statistically (p= 0.003) raised 32 (13.7%) over that of T. vaginalis infection 13 (5.6%). Co-infections were observed in only 2 (4.4%) of overall positives. No significant associations were observed between these infections and women age categories. Women had history of miscarriages and those had university levels were statistically linked (p<0.05) to the two infection agents although the former was only linked (p<0.05) to T. vaginalis infection. T. vaginalis infection was the only agent driving significance (p<0.05) when associated with vaginal secretion presence. Overall occurrence of T. vaginalis and Candida spp infections revealed in the present work was relatively high. Interestingly, a number of significant association between both infection profiles and women’s risk factors was also observed.